2014
DOI: 10.1007/s12205-013-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Compacted Lime — (Well-graded) Soil columns: Large scale tests and numerical modelling

Abstract: This study presents the results of large scale laboratory model tests to investigate the behavior of Compacted Lime-Well-graded Soil (CL-WS) rigid stone columns in soft soils. Tests were carried out on composite specimens to evaluate the influence of different parameters such as: the diameter of the column, the slenderness ratio, area ratio and the shear strength of the surrounding soil. Finite element analysis has been also performed using PLAXIS software to compare the results of numerical and experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The load carrying capacity is maximum at L/D ratio of 4 and decreases with increase in L/D ratio from 5 to 7. A similar type of response has been reported for compacted lime soil columns and stone columns by [2,26]. The bearing capacity failures were observed beyond critical column length (L) of 4D which decreases load carrying capacity of treated soil, so increasing column length beyond critical column length is counterproductive.…”
Section: Soil Samples Treated With Single Lime Column (Entire Area Loaded)supporting
confidence: 65%
See 1 more Smart Citation
“…The load carrying capacity is maximum at L/D ratio of 4 and decreases with increase in L/D ratio from 5 to 7. A similar type of response has been reported for compacted lime soil columns and stone columns by [2,26]. The bearing capacity failures were observed beyond critical column length (L) of 4D which decreases load carrying capacity of treated soil, so increasing column length beyond critical column length is counterproductive.…”
Section: Soil Samples Treated With Single Lime Column (Entire Area Loaded)supporting
confidence: 65%
“…Wong [25] worked on various case studies and theoretical studies and concluded that lime columns/piles increase strength and stiffness of in situ soils and the resulting increase in shear strength with lime columns was higher than the theoretical prediction. Malekpoor and Poorebrahim [26] concluded that compacted lime-well graded soil columns reduces the settlement and increases the load carrying capacity of the surrounding soil. It was also concluded that the variations in stiffness become negligible with column diameters greater than 100 mm so the results can be extrapolate for predicting the behavior of full size columns.…”
Section: Introductionmentioning
confidence: 99%
“…The type and size of the SC materials play an important role in governing the load-settlement behaviour of the SC stone since they affect the strength parameters. The impact of using alternative materials to constructs SC's was appraised in several studies [14,25,28,38,50,53]. The stronger the material, the better the performance of the SC.…”
Section: Sc Materialsmentioning
confidence: 99%
“…Liu et al [17] studied the thermal characteristics of the quicklime (CaO) energy pile thawing on the warm frozen soil surface and pointed out that the same life lime pile has different thawing effects on different types of frozen soil, and the expansion effect of the pile can increase the density of the soil around the quicklime pile to improve the strength of the ground. Malekpoor and Poorebrahim [18] carried out the experimental study on the functional characteristics of the lime pile in soft soil. Wang et al [19] studied the dynamic characteristics of lime-treated expansive soil and discussed the influence of different water contents, confining pressures, vibration frequencies, and other factors on the dynamic characteristics of the soil.…”
Section: Introductionmentioning
confidence: 99%